Effect of fiber length variations on mechanical and physical properties of coir fiber reinforced cement-albument composites (CFRCC) - Ahmad, Zuraida; Sarifuddin, Nurshahida; Iis, Sopyan; Halim, Zahurin (IIUM Press, 2011)
This paper evaluated the effect of fiber length on the mechanical and physical performance of coir fiber reinforced cement-a1humen composites (CFRCC). Albumen protein was added as a hinder and the coir fibers with the lengths of 0 (control cement composite). 2.5. 5, 10 and 20 mm was used as partial replacement of the cement mixture. Flexural and compressive strength, hulk density, moisture content and water absorption were investigated. The experimental investigations revealed that increasing in length of fiber increase the tlexura1 strength. Incorporation of long fiber into the cement paste however, decreased the workability and thus introduced voids which resulted in low density. In fact, the water absorption and moisture content were also increased.